2021
DOI: 10.35848/1882-0786/abe656
|View full text |Cite
|
Sign up to set email alerts
|

Nanocomposite fabricated by low energy silver ions implanted into dielectrics and sensitive to the refractive index of overlay

Abstract: Based on 30 keV silver ions at a fluence of 6 × 1016 ions·cm−2 implanted into SiO2, Al2O3 and YAG, we found that the nanocomposite layers embedded with silver nanoparticles are sensitive to the refractive index of overlays on the implanted surface. By dropping liquids with different refractive indices on the surface of nanocomposite layer, the reflection spectra of the rear surface would shift. The sample with YAG as the substrate has better performance by comparing with the other two samples. The prepared str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…From figure 1(a), it can be clearly found that when the overlay is air, Ag/SiO 2 sample presents an asymmetrical reflection peak at 435 nm (an abbreviation of λ=435 nm, denoting a position in wavelength λ). Similar reflection peak, as far as we know, is impossible to appear in a virgin SiO 2 slab [24], but it is quite evident in the soda-lime silicate glass implanted with Ag ions [23]. Therefore, the asymmetrical reflection peak at 435 nm is no other than the characteristic signal we expect in that its appearance is only because of the Ag ion implantation.…”
Section: Resultsmentioning
confidence: 53%
See 1 more Smart Citation
“…From figure 1(a), it can be clearly found that when the overlay is air, Ag/SiO 2 sample presents an asymmetrical reflection peak at 435 nm (an abbreviation of λ=435 nm, denoting a position in wavelength λ). Similar reflection peak, as far as we know, is impossible to appear in a virgin SiO 2 slab [24], but it is quite evident in the soda-lime silicate glass implanted with Ag ions [23]. Therefore, the asymmetrical reflection peak at 435 nm is no other than the characteristic signal we expect in that its appearance is only because of the Ag ion implantation.…”
Section: Resultsmentioning
confidence: 53%
“…The above findings indirectly support our opinion that the slight nonlinearity of Ag/SiO 2 sample is indeed attributed to the large current density adopted in the Ag ion implantation. Based on this opinion, Ag/SiO 2 sample was reproduced on a LC22-1C0-01 implanter by reducing the current density from 4.0 μA•cm −2 to 0.85 μA•cm −2 and keeping other parameters unchanged [24]. The observations revealed that in the reproduced sample, a continuous increase in refractive index of overlay from 1.000 to 1.539 led to a nearly linear decrease in position of characteristic signal from 479 nm to 445 nm.…”
Section: Resultsmentioning
confidence: 99%